2021
DOI: 10.1186/s13011-021-00408-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxic Effects of the New Psychoactive Substance “Voodoo” among Patients presented to the Poison Control Center of Ain Shams University Hospitals (PCC-ASUH), Egypt, during 2017

Abstract: Background Voodoo is a heterogeneous mixture of psychoactive substances that has recently grown in popularity among youth in Egypt. Patients can present with a variety of manifestations that may lead to death in some cases. This study assessed the acute toxic effects of voodoo among patients presented to the Poison Control Center of Ain Shams University Hospitals (PCC-ASUH) during a one year period. Methods This is a retrospective study of all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In Northern Africa, the smoking of hashish and the chewing of Kath has become very rampant. Although there is little data from the region regarding the prevalence and patterns of use of novel psychoactive substances; reports from studies carried out in Egypt have suggested that the estimated prevalence of novel psychoactive substance use among adolescents in the country are largely underestimated[ 96 ]. However, tabloid reports have called attention to an increasing demand and use of novel psychoactive substances including “voodoo” and “strox” among adolescents and young adult in Egypt[ 97 , 98 ].…”
Section: Epidemiology Of Substance Use Across the African Continentmentioning
confidence: 99%
See 1 more Smart Citation
“…In Northern Africa, the smoking of hashish and the chewing of Kath has become very rampant. Although there is little data from the region regarding the prevalence and patterns of use of novel psychoactive substances; reports from studies carried out in Egypt have suggested that the estimated prevalence of novel psychoactive substance use among adolescents in the country are largely underestimated[ 96 ]. However, tabloid reports have called attention to an increasing demand and use of novel psychoactive substances including “voodoo” and “strox” among adolescents and young adult in Egypt[ 97 , 98 ].…”
Section: Epidemiology Of Substance Use Across the African Continentmentioning
confidence: 99%
“…“Voodoo” is a heterogeneous mixture of several psychoactive substances, including synthetic cannabinoids, tramadol, amphetamine, methadone, benzodiazepines, penitrem A (a neurotoxin) and morphine derivatives. The concentrations of the chemical constituents and adulterants of voodoo also vary substantially among the different clandestine laboratories that produce it[ 96 , 99 ]. Another novel psychoactive substance that is gaining popularity in Egypt is “Strox”[ 100 ].…”
Section: Epidemiology Of Substance Use Across the African Continentmentioning
confidence: 99%
“…Strox and Voodoo are considered two of the most popular blends of NPS in the Egyptian drug market. These NPSs are usually made in clandestine laboratories with substantial variation in the types and concentrations of chemical constituents and adulterants, further contributing to the variation in clinical presentation ( Hussien et al., 2021 ). They have also demonstrated that sample Voodoo NPS has a broad spectrum of various previously identified bioactive compounds, including quinazolines, morphinan alkaloid, cannabinoids, penitrem A and the well-known synthetic cannabinoid FUB-AMBcn ( Hussien et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%